Effects of different exercise modalities and intensities on body composition in overweight and obese children and adolescents: a systematic review and network meta-analysis - Huang, Zan; Li, Jiayu; Liu, Yanjie; Zhou, Yulan (Frontiers in Physiology, 2023)
Background: Childhood and adolescent overweight and obesity are global public health issues. Exercise is one of the significant health and fitness strategies used to manage obesity. However, previous studies on exercise and overweight and obese children have produced inconsistent findings and lacked comparisons between different exercise modalities and intensities. Therefore, a network meta-analysis is necessary to provide evidence-based intervention programs for overweight and obese children and adolescents.Objective: Identify the effects of different intensity exercise modalities on changes in body composition in overweight and obese children and adolescents.Methods: A search for randomized controlled trials was conducted on Web of Science, PubMed, Scopus, and Embase involving exercise interventions aimed at improving body composition (body fat percentage, BMI, fat mass, fat-free mass, body weight) in overweight and obese children and adolescents. A random-effects network meta-analysis was performed using STATA 14.0 software within a frequentist framework. The literature quality was assessed using the Cochrane Risk of Bias Tool 2.0.Results: Thirty-two papers involving 1452 participants were included. There were six types of intervention involved in the study, including moderate-intensity aerobic exercise, high-intensity aerobic exercise, moderate-intensity resistance exercise, high-intensity resistance exercise, moderateintensity combined exercise, and high-intensity combined exercise. The network meta-analysis results revealed that high-intensity combined exercise was the best exercise mode for improving BMI [mean difference in kg/m 2 =-1.65, 95% CI (-3.27, -0.02)] and reducing fat mass [mean difference in kg=-2.87, 95% CI (-4.84, -0.91)]. Moderate intensity combined exercise was the best mode for weight loss [mean difference in kg =-4.58, 95% CI (-5.94, -3.22)] and improvement in body fat percentage [mean difference in %=-2.52, 95% CI (-3.83, -1.20)]. High-intensity resistance exercise had the optimal effect in increasing fat-free mass [mean difference in kg =1.10, 95% CI (0.22, 1.99)].In conclusion, the study found that combined exercise, whether moderate or high intensity, was more effective than any other exercise modality in improving body fat percentage and This is a provisional file, not the final typeset article BMI, reducing fat mass and weight. Resistance exercise was the most effective in increasing fat-free mass.The study was registered with PROSPERO, with registration number CRD42023403600.